Penyuluhan Hukum: Dampak Negatif Judi Online dan Pinjaman Online - Encep Saefullah; Muflihah Muflihah; Bambang Dwi Suseno; Gatot Hartoko; April Laksana; Alhane Wahdaliansyah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
In Indonesia, there has been a lot of news reporting criminal acts carried out by teenagers, one of which is currently popular or becoming a trend is online gambling or slots. Online gambling has also been categorized as a cyber crime or criminal act via internet technology. Apart from online gambling, one of the trends that is currently widespread is pinjol (online loan) services. These two phenomena, which are currently a national problem, have raised concerns from the Government and all levels of society in Pulosari District, Pandeglang Regency, so serious efforts are needed from all parties, both the government, the community and parents. This service activity aims to provide education to the community in the form of legal counseling to increase the community's legal understanding and awareness about the negative impacts of online gambling and online loans in Pulosari District, Pandeglang Regency. The implementation method starts from literature review, field observations and legal counseling. The results of this activity increased knowledge, understanding and awareness of the people of Pulosari District about the negative impacts of online gambling and online loans.